Handbook of emergency response : a human factors and systems engineering approach - Racz, LeeAnn; Badiru, Adedeji Bodunde, 1952- (CRC Press, 2025)
"Despite pre-emptive preparations, disasters can and do occur and are a fact of life. Whether natural disasters, catastrophic accidents, or terrorist attacks, the risk cannot be completely eliminated. A carefully prepared response is your best defense. This fully updated second edition of Handbook of Emergency Response presents practical advice and guidelines on how to plan the coordinated execution of emergency response. This handbook incorporates human factors and a systems engineering approach in emergency response project management. It provides cutting-edge research in developing a systematic structure for communication, cooperation, and coordination. Managing a project in the wake of a tragedy is complicated and involves various emotional, sentimental, reactive, and chaotic responses. This is the time that a structured communication model is most needed. This second edition includes important lessons learned and developments since the first edition was published, as well as additional information devoted to systems thinking and industrial engineering in planning for responses to emergencies. The reader will develop a thorough understanding of how to handle an emergency response using a systems approach. The handbook is an ideal purchase for any student or practitioner of human factors, safety, systems engineering, events management, local or federal governance or those in the emergency services"-- Provided by publisher.
"First edition published by CRC Press 2013"--Title page verso.
Keywords: Emergency management -- Technological innovations.; Rescue work.; Survival and emergency equipment.; Incident command systems.; Human engineering.; elektronické knihy; electronic books